Effect of thinning on LAI variance in heterogeneous forests - Davi, H.; Baret, F.; Huc, R.; Dufrêne, E. (Forest Ecology and Management, 2008)
Leaf Area Index (LAI) is a main variable controlling carbon and water ﬂuxes. This paper estimated the effect of thinning on the spatial distribution of leaf area in French forests. While many studies have focused on average LAI, we estimated clumping and measured both average LAI and the variation around it. LAI was derived from digital hemispherical photos at three sites: an unmanaged Fagus sylvatica forest in temperate area (control site), a mixed Mediterranean forest of Quercus ilex and Pinus halepensis, and regeneration of F. sylvatica under a mature stand of Pinus nigra in mountainous area. LAI measurements were also made with LAI 2000 devices over 5 years (from 1994 to 1998) within forest stands dominated by either beech (F. sylvatica L.), by oaks (Quercus petraea (Matus) Liebl., Quercus robur(Matus) Liebl.), or by Scots Pine (Pinus sylvestris L.). Thinning led to a variable decrease in LAI. The coefﬁcient of variation of LAI (CVLAI ) provided a useful ecological index of the level and type of thinning. For undisturbed stands, CVLAI varied from 10% to 20%, corresponding to the higher average LAI values. Disturbances created by thinning increase LAI spatial variability, resulting in larger CVLAI values for all stands considered. Possible explanations of these results and use in remote sensing were discussed.
Keywords: Ecological index; Ecosystem trait; Forest disturbance; forest ecosystems; heterogeneity; leaf area index; thinning

Effect of thinning on LAI variance in heterogeneous forests - Davi, H.; Baret, F.; Huc, R.; Dufrêne, E. (Forest Ecology and Management, 2008)
Leaf Area Index (LAI) is a main variable controlling carbon and water ﬂuxes. This paper estimated the effect of thinning on the spatial distribution of leaf area in French forests. While many studies have focused on average LAI, we estimated clumping and measured both average LAI and the variation around it. LAI was derived from digital hemispherical photos at three sites: an unmanaged Fagus sylvatica forest in temperate area (control site), a mixed Mediterranean forest of Quercus ilex and Pinus halepensis, and regeneration of F. sylvatica under a mature stand of Pinus nigra in mountainous area. LAI measurements were also made with LAI 2000 devices over 5 years (from 1994 to 1998) within forest stands dominated by either beech (F. sylvatica L.), by oaks (Quercus petraea (Matus) Liebl., Quercus robur(Matus) Liebl.), or by Scots Pine (Pinus sylvestris L.). Thinning led to a variable decrease in LAI. The coefﬁcient of variation of LAI (CVLAI ) provided a useful ecological index of the level and type of thinning. For undisturbed stands, CVLAI varied from 10% to 20%, corresponding to the higher average LAI values. Disturbances created by thinning increase LAI spatial variability, resulting in larger CVLAI values for all stands considered. Possible explanations of these results and use in remote sensing were discussed.
Keywords: Ecological index; Ecosystem trait; Forest disturbance; forest ecosystems; heterogeneity; leaf area index; thinning